Kinerja Keuangan Perusahaan Sebelum dan Sesudah Kenaikan Harga Bahan Bakar Minyak (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Suparno Suparno (Jurnal Telaah dan Riset Akuntansi, 2015)
The purpose of this research is to determine the financial performance of emiten before and after the increasing of fuel price in manufacturing corporation which already listed in BEI. Population of this research is 144 companies delisted in Indonesian Stock Exchange. Sample is generated by using Slovin formula and 59 companies fullfiled criteria as samples in this research.. Liquidity and profitability are dimensions used to analize companies’ financial performance. Using paired sample t-test to analize the financial performance before and after fuel increasing price. The result of the research show that not all of the dimensions is mentioned to analized the companies financial performance. A significant differences shown by activity dimension. Liquidity and profitability dimensions shown no significant differences on financial performance before and after the incremental of fuel prices.KEYWORDS :  financial performance, fuel prices